2016
DOI: 10.1136/bmjopen-2016-011205
|View full text |Cite
|
Sign up to set email alerts
|

Talking about human papillomavirus and cancer: protocol for a patient-centred study to develop scripted consultations

Abstract: IntroductionPersistent infection with sexually transmitted, high-risk human papillomavirus (HPV) types is the cause of all cervical cancers and some anogenital and oropharyngeal cancers. HPV is an extremely common asymptomatic infection but little known and poorly understood by the public. Patients with HPV-related cancers have new and challenging information needs due to the complex natural history of HPV and the stigma of sexual transmission. They may ask questions that are outside the remit of the tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…As many clinicians can attest, guiding a nonsmoking, physically active 50‐year‐old with low‐volume, HPV‐associated OPC through the treatment decision‐making process is increasingly complex . In the scenario in which various curative treatment options exist and functional outcomes are prioritized, decisional conflict can arise with the potential for decisional regret among survivors .…”
Section: Introductionmentioning
confidence: 99%
“…As many clinicians can attest, guiding a nonsmoking, physically active 50‐year‐old with low‐volume, HPV‐associated OPC through the treatment decision‐making process is increasingly complex . In the scenario in which various curative treatment options exist and functional outcomes are prioritized, decisional conflict can arise with the potential for decisional regret among survivors .…”
Section: Introductionmentioning
confidence: 99%
“…The methods for this study are described in detail in a protocol paper published during the data collection period 20 and a schematic overview is presented in figure 1 . In brief, consultation guides were developed in two stages and tested in a third.…”
Section: Methodsmentioning
confidence: 99%
“…There is therefore an urgent need to ensure that primary care staff are adequately trained to communicate with women about these changes, as previous research has shown that discussions about HPV can be seen as a “can of worms” (McSherry et al., ). One approach is the development of scripted consultations to help clinicians in these conversations (Hendry et al., ).…”
Section: A New Era For Cervical Screeningmentioning
confidence: 99%
“…One approach is the development of scripted consultations to help clinicians in these conversations (Hendry et al, 2016).…”
Section: A New Era For Cervical Screeningmentioning
confidence: 99%